2022
DOI: 10.3389/fgene.2022.898507
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Necroptosis-Related LncRNA Signature in Hepatocellular Carcinoma for Prognosis Estimation and Microenvironment Status

Abstract: Background: Hepatocellular carcinoma (HCC) is among malignancies with the highest fatality toll globally and minimal therapeutic options. Necroptosis is a programmed form of necrosis or inflammatory cell death, which can affect prognosis and microenvironmental status of HCC. Therefore, we aimed to explore the prognostic value of necroptosis-related lncRNAs (NRLs) in HCC and the role of the tumor microenvironment (TME) in immunotherapy.Methods: The RNA-sequencing data and clinical information were downloaded fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Recently, lncRNAs have been identified as critical factors in cancer development [ 59 , 60 ]. In this study, firstly we found that the prediction model of NMRGs was not so good (AUC = 0.447).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, lncRNAs have been identified as critical factors in cancer development [ 59 , 60 ]. In this study, firstly we found that the prediction model of NMRGs was not so good (AUC = 0.447).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that lncRNAs take on an essential significance in the progression and development of various cancers including HCC [13,26,27]. Furthermore, previous studies have built and proven ferroptosis-associated, autophagy-associated, and necroptosis-associated lncRNA prognosis signatures for cancers [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA HEPFAL accelerates ferroptosis in HCC by regulating SLC7A11 ubiquitination [13] .The necroptosisrelated lncRNA signature in HCC for prognosis estimation and microenvironment status has been identi ed and validated [14] . Overexpression of the lncRNA HOTAIRM1 promotes lenvatinib resistance by downregulating miR-34a and activating autophagy in HCC [15] .…”
Section: Introductionmentioning
confidence: 99%